Implementation of the Apriori Method for Analysis of Hotel Guest Visit Patterns at the Rio Asri Hotel Bengkulu - Rodi Rodi; Liza Yulianti; Juju Jumadi (Jurnal Komputer, Informasi dan Teknologi, 2022)
Analysis of the pattern of guest visits at the Rio Asri Bengkulu Hotel with the a priori algorithm is carried out to obtain rules and predict the next guest visit and provide guests with marketing rewards to increase the interest of other visitors in utilizing and using hotel services regularly or periodically. A priori analysis is defined as a process to find all the rules that meet the minimum requirements for support and the minimum requirements for confidence. The implementation of the system uses the Visual Basic 2010 programming language and the method used in this study is the waterfall method. The results of the analysis carried out with the variables used are arrival time, number of guests, area of ​​origin and class of room chosen by guests, it is found that the itemset with the best pattern is influenced by the specified minimum support value.